Modelo de environmental, social, governance e práticas integradas de ESG+ para o setor da construção civil - Fros, Camila Saccol (2024)
Analyzing the different perceptions in relation to Civil Construction (significant contributor to the Gross Domestic Product – GDP – however is responsible for 35% of global emission of Carbon Dioxide emissions), the sector has been adding strategies with the international sustainability movement, aiming of building consciously, mitigate negative consequences, through more responsible strategies, seeking to impact positively people's lives. This dissertation aims to develop an ESG+ implementation model and guidelines that qualify the sustainability practices of companies in the sector, aiming to improve aspects of environmental, social and governance performance, aiming to identify effective strategies for sustainability. To achieve this objective, 4 specific approaches and 4 sources of evidence were outlined in 5 companies: a) Systematic Literature Review; b) Analysis of reports; c) Interviews; d) study cases. The main results include: an SLR, allowed us to understand the advancement in the topic, especially the role of ESG to qualify performance and market drivers; by the reports from high-performance construction companies and sustainable recognized in the country, it was possible to have an overview of their activities in terms of ESG; the interviews allowed for a closer view at the companies practices; and the last phase of the case study, through in loco visits in two of them, provided a recent view of the companies, being one with open capital and the other privately traded. Finally, a model with guidelines and proposals for developing practices related to ESG+ in construction companies was presented. The research will provide an insight into how construction companies are acting in relation to Environmental, Social, Governance and Integrated Practices (ESG+), verifying the innovative development of the Civil Construction sector, as well as creating a starting point to outline actions for companies that aim to develop ESG+.